A new model of the carbonator reactor in the calcium looping technology for post-combustion CO2 capture. (15th November 2015) - Ortiz, C.; Chacartegui, R.; Valverde, J.M.; Becerra, J.A.; Perez-Maqueda, L.A.
Highlights: A new carbonator model is proposed taking into account realistic CaL conditions. Carbonation in the diffusion stage is considered to predict the capture efficiency. High capture efficiency may be achieved by operating with high particles residence time. New model allows accurate modelling for extended residence's time. Results are in good agreement with data from pilot-scale tests. Abstract: The Ca-Looping (CaL) process is considered as a promising technology for CO2 post-combustion capture in power generation plants yielding a minor penalty on plant performance as compared with other capture technologies such as conventional amine-based capture systems. This manuscript presents a new carbonator reactor model based on lab-scale multicyclic CaO conversion results, which take into account realistic CaO regeneration conditions that necessarily involve calcination under high CO2 partial pressure and high temperature. Under these conditions, CaO conversion in the diffusion controlled stage is a relevant contribution to the carbonation degree during typical residence times. The main novelty of the model proposed in the present work is the consideration of the capture efficiency in the diffusion controlled phase of carbonation. It is demonstrated that increasing the residence time by a few minutes in the carbonator yields a significant improvement of the capture efficiency. Model predictions are shown to agree with experimental results retrieved from pilot-scale tests. The new model allows a more accurate evaluation and prediction of carbonator's performance over a wider range of residence times. The results obtained may be relevant for the optimization of CaL operation parameters to be used in real power plants.